2005
DOI: 10.1083/jcb.200508072
|View full text |Cite|
|
Sign up to set email alerts
|

Expression of mutant huntingtin in glial cells contributes to neuronal excitotoxicity

Abstract: Huntington disease (HD) is characterized by the preferential loss of striatal medium-sized spiny neurons (MSNs) in the brain. Because MSNs receive abundant glutamatergic input, their vulnerability to excitotoxicity may be largely influenced by the capacity of glial cells to remove extracellular glutamate. However, little is known about the role of glia in HD neuropathology. Here, we report that mutant huntingtin accumulates in glial nuclei in HD brains and decreases the expression of glutamate transporters. As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
376
2
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 414 publications
(403 citation statements)
references
References 48 publications
20
376
2
5
Order By: Relevance
“…However, the expression of mHTT in neurons alone cannot recapitulate the key features of HD (Gu et al, 2005). Indeed, mHTT is accumulated in astrocytes, whose function is altered in HD (Shin et al, 2005). Astrocytic glutamate uptake is defective in the R6/2 HD mouse model, where levels of EAAT2 are reduced, leading to increase in striatal extracellular glutamate and excitotoxicity (Maragakis and Rothstein, 2001).…”
Section: Astrocytes In the Diseased Brain Are Central To Neuropathologymentioning
confidence: 99%
“…However, the expression of mHTT in neurons alone cannot recapitulate the key features of HD (Gu et al, 2005). Indeed, mHTT is accumulated in astrocytes, whose function is altered in HD (Shin et al, 2005). Astrocytic glutamate uptake is defective in the R6/2 HD mouse model, where levels of EAAT2 are reduced, leading to increase in striatal extracellular glutamate and excitotoxicity (Maragakis and Rothstein, 2001).…”
Section: Astrocytes In the Diseased Brain Are Central To Neuropathologymentioning
confidence: 99%
“…11,12 Mutant HTT is expressed in glial cells, 13,14 and transgenic mice overexpressing mutant HTT in astrocytes show age-dependent neurological symptoms. 15,16 Additionally, primary astrocytes overexpressing full-length human mutant HTT show reduced mRNA levels of cholesterol biosynthetic genes, along with impaired cellular production and secretion of apoE.…”
mentioning
confidence: 99%
“…This phenomenon has led to extensive studies of mutant huntingtin on neurons. Later studies have found that in a neuron-glia co-culture system, wild-type glial cells protect neurons against neurotoxicity caused by mutant Htt, whereas glial cells expressing mutant Htt increased neuronal vulnerability [2] . These studies indicate that cell-cell interactions between neurons and glial cells play an important role in HD pathology [3,4] .…”
Section: Introductionmentioning
confidence: 99%
“…On the membranes of astrocytes, which are the major subtype of glial cells, there are two types of glutamate transporters (GLT-1 and GLAST) that do most of the work in clearing extracellular excitatory neurotransmitters [7,8] . It has been shown that small fragments of N-terminal mutant Htt (such as N-208, N-171), which were reported to be more pathogenic than full-length mutant Htt, caused decreased expression of GLT-1 [2,5] . However, these fragments had been cut occasionally and might not exist in physiological and pathological conditions, so they could not simulate the condition of HD patients completely.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation